IDENTIFICATION, INTENSITY AND PREVALENCE OF ECTOPARASITES IN THE BLUE SWIMMING CRAB, Portunus pelagicus (Linn, 1758) CAPTURED AT SELECTED STATIONS IN EAST LAMPUNG IN WESTERN SEASON - Fidyandini, Hilma Putri; Setyawan, Agus; Malau, Victor Pandpotan (University of Lampung, 2024)
Based on data from KKP, Indonesia recorded the value of crab meat exports in2017 ranked 3rd largest after Tuna and shrimp, namely by value nearly 411 million. This makes the crab catching volume increased. But there is a quality crab that is not always in condition good because of the disease that often attacks crab. Disease caused by parasites that affect population reduction and decrease in body weight of the organism, this is what causes the occurrence of consumer rejection. Attacks from ectoparasites can cause harm organs in the host organism, among others, damage to the body surface and the gills of the host. This study aims to find out identification, intensity and prevalence of ectoparasites found in crab in Margasari Village Waters, Labuhan Maringgai District, East Lampung Regency. This study includes taking 40 crab samples obtained from the catch of fishermen from two stations, Panceran and Gambas stations. The data of ectoparasite samples found from the examination results are then recorded and for ectoparasite attacks on crab can be analyzed by counting prevalence and intensity. Crab ectoparasites identified in the Margasari village, Labuhan Maringgai, East Lampung Regency, among others Octolasmis sp., Chelonibia sp., and Thompsonia sp. In this study Thompson sp. it is the highest intensity crab ectoparasite, amounting to 471 / individual while Chelonibia sp. the Panceran station has a moderate prevalence of 33%, and other ectoparasites have low prevalence throughout the station